Methods of Adaptive Fuzzy Control of Robots Based on Neural Networks - Kostrova, H. (Черкаського національного університету імені Богдана Хмельницького, 2023)
Uncertainty plays a significant role in many management processes that arise in practice. Stochastic control techniques have been applied to problems in which the uncertainty is due to chance, while fuzzy control extends our consideration to the domains of imprecision and uncertainty.
Keywords: fuzzy control; robots; neural networks